Identification of ZNF366 and PTPRD as novel determinants of plasma homocysteine in a family-based genome-wide association study. - Mälarstig, A; Buil, A; Souto, J; Clarke, R; Blanco-Vaca, F; Fontcuberta, J; Peden, J; Andersen, M; Silveira, A; Barlera, S; Seedorf, U; Watkins, H; et al. (2009)
Total plasma homocysteine concentration (tHcy) is a biomarker for atherothrombotic disease, but causality remains uncertain. Polymorphisms in the genes involved in methionine metabolism explain only a small fraction of the heritability of tHcy levels. In a genome-wide association study, we examined the genetic determinants of tHcy using a 2-stage design. First, 283 437 single nucleotide polymorphisms (SNPs) were tested for association with tHcy in 387 persons recruited from 21 large Spanish families. Of those, 17 SNPs showed equal or stronger association with tHcy level compared with the MTHFR 677C>T SNP (beta = 0.10, P = .0001). Second, a replication analysis of these 17 SNPs was performed in patients with premature myocardial infarction (n = 1238). Novel associations were found for SNPs near the ZNF366 gene (lead SNP rs7445013; discovery stage: adjusted beta = -0.12, P = 5.30 x 10(-6), replication stage: adjusted beta = -0.13, P = .004) and the PTPRD gene (lead SNP rs973117; discovery stage: adjusted beta = 0.11, P = 5.5 x 10(-6), replication stage: adjusted beta = 0.10, P = .005). These associations were independent of known confounders, including creatinine clearance and plasma fibrinogen concentration. Our findings implicate novel pathways in homocysteine metabolism, and highlight the need for investigation of the associated genes in the etiology of vascular diseases.